DRO1 influences root system architecture in Arabidopsis and Prunus species. (March 2017) - Guseman, Jessica M.; Webb, Kevin; Srinivasan, Chinnathambi; Dardick, Chris
Summary: Roots provide essential uptake of water and nutrients from the soil, as well as anchorage and stability for the whole plant. Root orientation, or angle, is an important component of the overall architecture and depth of the root system; however, little is known about the genetic control of this trait. Recent reports in Oryza sativa (rice) identified a role for DEEPER ROOTING 1 ( DRO1 ) in influencing the orientation of the root system, leading to positive changes in grain yields under water‐limited conditions. Here we found that DRO1 and DRO1 ‐related genes are present across diverse plant phyla, and fall within the IGT gene family. The IGT family also includes TAC1 and LAZY1, which are known to affect the orientation of lateral shoots. Consistent with a potential role in root development, DRO1 homologs in Arabidopsis and peach showed root‐specific expression. Promoter–reporter constructs revealed that AtDRO1 is predominantly expressed in both the root vasculature and root tips, in a distinct developmental pattern. Mutation of AtDRO1 led to more horizontal lateral root angles. Overexpression of AtDRO1 under a constitutive promoter resulted in steeper lateral root angles, as well as shoot phenotypes including upward leaf curling, shortened siliques and narrow lateral branch angles. A conserved C‐terminal EAR‐like motif found in IGT genes was required for these ectopic phenotypes. Overexpression of PpeDRO1 in Prunus domestica (plum) led to deeper‐rooting phenotypes. Collectively, these data indicate a potential application for DRO1 ‐related genes to alter root architecture for drought avoidance and improved resource use. Significance Statement: Root orientation is an architectural trait that can greatly influence the overall depth of a root system, but little is known about the genetic control of this trait. Here we demonstrate that expression of DEEPER ROOTING genes is important for lateral root angle in the model plant Arabidopsis and for root system depth in plum. We suggest that manipulating DRO1 expression will be useful for altering root architecture in crops.